(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
The article presents a literature review of the epidemiology, pathogenesis and significance of increased risk of cardiovascular disease in patients with diabetes and prediabetes . The hyperglycemia and insulin resistance seen in diabetes and pre-diabetes results in an increase in reactive oxygen species, which triggers intracellular molecular signaling. The resulting prothrombotic the state and increase in inflammatory mediators accelerate atherosclerotic changes and the development of macrovascular complications. Individuals with diabetes or pre-diabetes have a higher risk of developing myocardial infarction, stroke, and peripheral arterial disease.